PIC controlled induction heating using resonant technique / Fatimah Rusbiahty Ahmad - Ahmad, Fatimah Rusbiahty (2008)
An induction heating controller circuit based on resonant technique is presented. The controller is developed using Peripheral Interface Controller (PIC) chip and Insulated Gate Bipolar Transistor (IGBT) as the main switching devices. The performance of circuit is compared in terms of power losses occur in the main power switching devices. PSpice simulation software is used to simulate and evaluate the circuit performance. Hard switching and soft switching techniques are also investigated. From the simulation results obtained, the best circuit topology and switching technique are selected and implemented using the Peripheral Interface Controller (PIC) chip as main controller. The laboratory model of the system is developed and tested as a portable cooker powered with DC power supply. The performance of the portable cooker is compared with the conventional hot plate technique. The proposed system is also applicable with AC power supply. Simulation results with an AC supply show the proposed technique is able to produce high frequency output current with less harmonics distortion injected back to the AC supply.